2011
DOI: 10.1177/0961203311399607
|View full text |Cite
|
Sign up to set email alerts
|

Association of heart structure and function abnormalities with laboratory findings in patients with systemic lupus erythematosus

Abstract: Conventional risk factors of coronary artery disease fail to explain the increased frequency of cardiovascular morbidity in patients with systemic lupus erythematosus (SLE). The study was conducted to determine possible association between the heart structure and function abnormalities with established prognostic value assessed by non-invasive imaging techniques and markers of autoimmune and inflammatory phenomena typical for SLE. Echocardiography and single photon emission computerized tomography (SPECT; Tc-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
1
16
1
Order By: Relevance
“…30 Moreover, levels of aCL and anti-β2GPI autoantibodies were also associated with myocardial perfusion defects detected by single-photon emission computed tomography, but not in the distribution of major coronary arteries, suggesting that APA may also cause small, undetected thrombi in the coronary microcirculation. 31 …”
Section: Antiphospholipid Antibodies Rheumatoid Arthritis-related Aumentioning
confidence: 99%
“…30 Moreover, levels of aCL and anti-β2GPI autoantibodies were also associated with myocardial perfusion defects detected by single-photon emission computed tomography, but not in the distribution of major coronary arteries, suggesting that APA may also cause small, undetected thrombi in the coronary microcirculation. 31 …”
Section: Antiphospholipid Antibodies Rheumatoid Arthritis-related Aumentioning
confidence: 99%
“…A few studies have reported risk factors associated with the presence of PAH in patients with SLE. Some studies found a higher prevalence of Raynaud's phenomenon and antiphospholipid antibody , and shorter disease duration in SLE patients with PAH compared to those without; however, these associations were not confirmed in other studies . Therefore, the clinical variables related to PAH in SLE patients and its underlying pathogenic mechanisms remain to be determined.…”
Section: Introductionmentioning
confidence: 84%
“…SLE is associated with verrucous Libman‐Sacks vegetations that affect the mitral valve most severely, but can affect other valves, the chordae tendinae, and the endocardium 4 . In a study by Plazak et al, echocardiographic studies revealed that up to 60% of SLE patients had pathological thickening of valvular tissue, which increased significantly with age 13 . Bouma et al examined Libman‐Sacks endocarditis, and concluded that while mitral valve repair is possible, it should only be recommended for younger patients with stable SLE that has not caused severe structural damage to the valve leaflets 14 .…”
Section: Discussionmentioning
confidence: 99%
“…4 In a study by Plazak et al, echocardiographic studies revealed that up to 60% of SLE patients had pathological thickening of valvular tissue, which increased significantly with age. 13 Bouma et al examined Libman-Sacks endocarditis, and concluded that while mitral valve repair is possible, it should only be recommended for younger patients with stable SLE that has not caused severe structural damage to the valve leaflets. 14 Secondary antiphospholipid syndrome (APS) is also commonly present in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%